Peran Mahasiswa Kuliah Kerja Nyata (KKN) dalam Kegiatan Pendampingan Pendidikan dan Keagamaan Sebagai Wujud Pegabdian Kepada Masyarakat - Pratama, Andi Putra Aditya; Azzahra, Fatimah; Nirwana, Nirwana; Arniati, Arniati; Putri, Nur Nadila; Harun, Diza Azizah Rezky; Islami, Muhammad Pasya Fadhil; Fadli, Muhammad; Kadir, Muh Ahyar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muslim Maros, 2024)
Field Work Lecture (KKN) is a concrete manifestation of the duties of lecturers and students in implementing the Tri Dharma of Higher Education, namely the aspects of education, research and service. Through community service activities in the Teppo area, synergy occurs between universities and the community as a form of emocratic knowledge. The aim of this service is to provide local communities with an understanding of the importance of education and religion in order to assist the government in educating the nation's children. Service is carried out through activities: KKN Teaching, BTQ Training, Yasinan, Sholeh Children's Festival, Extracurricular Training, Social Service and Community Competitions. The results of the service provide an illustration of increasing enthusiasm and increasing public understanding, especially teachers and parents, regarding educational accreditation instruments and religious values. From an early age, the importance of reading for children, guidance for studying the Al-Qur'an and learning process strategies as materials for teaching in the classroom.